Current Use of Asparaginase in Acute Lymphoblastic Leukemia/Lymphoblastic Lymphoma - Maese, Luke; Rau, Rachel E. (Frontiers in Pediatrics, 2022)
Pediatric Acute Lymphoblastic Leukemia (ALL) cure rates have improved exponentially over the past five decades with now over 90% of children achieving long-term survival. A direct contributor to this remarkable feat is the development and expanded understanding of combination chemotherapy. Asparaginase is the most recent addition to the ALL chemotherapy backbone and has now become a hallmark of therapy. It is generally accepted that the therapeutic effects of asparaginase is due to depletion of the essential amino acid asparagine, thus occupying a unique space within the therapeutic landscape of ALL. Pharmacokinetic and pharmacodynamic profiling have allowed a detailed and accessible insight into the biochemical effects of asparaginase resulting in regular clinical use of therapeutic drug monitoring (TDM). Asparaginase’s derivation from bacteria, and in some cases conjugation with a polyethylene glycol (PEG) moiety, have contributed to a unique toxicity profile with hypersensitivity reactions being the most salient. Hypersensitivity, along with several other toxicities, has limited the use of asparaginase in some populations of ALL patients. Both TDM and toxicities have contributed to the variety of approaches to the incorporation of asparaginase into the treatment of ALL. Regardless of the approach to asparagine depletion, it has continually demonstrated to be among the most important components of ALL therapy. Despite regular use over the past 50 years, and its incorporation into the standard of care treatment for ALL, there remains much yet to be discovered and ample room for improvement within the utilization of asparaginase therapy.